USM, UNTIRTA ENHANCING COOPERATION IN RESEARCH AND STUDENT EXCHANGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 28 April 2016 – Universiti Sains Malaysia (USM) today signed a Memorandum of Agreement (MoA) with Universitas Sultan Ageng Tirtayasa (UNTIRTA) Indonesia to enhance cooperation in areas of research and student exchange.